Simplify the Expression: a⁴a⁸a⁻⁷/a⁹ Using Exponent Rules

Question

a4a8a7a9=? \frac{a^4a^8a^{-7}}{a^9}=\text{?}

Video Solution

Solution Steps

00:00 This is the solution
00:09 In order to eliminate a negative exponent
00:12 We'll invert the numerator and denominator in order for the exponent to become positive
00:15 We'll apply this formula to our exercise
00:22 When multiplying powers with equal bases
00:25 The power of the result equals the sum of the powers
00:28 We'll apply this formula to our exercise, we'll then proceed to add up the powers
00:42 This is the solution

Step-by-Step Solution

Let's recall the law of exponents for multiplication between terms with identical bases:

bmbn=bm+n b^m\cdot b^n=b^{m+n} We'll apply this law to the fraction in the expression in the problem:

a4a8a7a9=a4+8+(7)a9=a4+87a9=a5a9 \frac{a^4a^8a^{-7}}{a^9}=\frac{a^{4+8+(-7)}}{a^{^9}}=\frac{a^{4+8-7}}{a^9}=\frac{a^5}{a^9} where in the first stage we'll apply the aforementioned law of exponents and in the following stages we'll simplify the resulting expression,

Let's now recall the law of exponents for division between terms with identical bases:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We'll apply this law to the expression we got in the last stage:

a5a9=a59=a4 \frac{a^5}{a^9}=a^{5-9}=a^{-4} Let's now recall the law of exponents for negative exponents:

bn=1bn b^{-n}=\frac{1}{b^n} And we'll apply this law of exponents to the expression we got in the last stage:

a4=1a4 a^{-4}=\frac{1}{a^4} Let's summarize the solution steps so far, we got that:

a4a8a7a9=a5a9=1a4 \frac{a^4a^8a^{-7}}{a^9}=\frac{a^5}{a^9}=\frac{1}{a^4} Therefore, the correct answer is answer A.

Answer

1a4 \frac{1}{a^4}